Multimedia electronic manual "Thermometry" - V. A. Dyachkov; A. O. Rubanenko; A. A. Garanin (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
Relevance. The education system plays a crucial role in the formation of professional orientation in the learning process. The digital transformation of education has become an integral part of the development of our society. One of the effective tools in the context of the activation of digital didactics to improve the quality of educational services is the introduction of modern distance learning technologies.Aim. Creation of a multimedia electronic manual dedicated to teaching the discipline "Propaedeutics of internal diseases" on the topic "Thermometry".Materials and methods. The multimedia electronic manual "Thermometry" developed at the Propaedeutic Therapy Department in Samara State Medical University contains theoretical material on the methodology and technique of measuring body temperature. The manual provides illustrative material with illustrations and description of the main types of fevers, describes the grades of fever, provides a detailed description of the rules for the registration of a temperature chart and provides an example of a filled temperature chart. The presented multimedia electronic manual contains a set of tests and clinical cases for self-monitoring of students' knowledge with references.Conclusion. The multimedia electronic manual "Thermometry" developed at Samara State Medical University can increase the efficiency of learning the material, which will help to improve the formation of professional competencies among students, while examining patients of various profiles, making correct diagnosis and management strategy.